Band engineering and absorption spectra in compressively strained Ge0.92Sn0.08/Ge (001) double quantum well for infrared photodetection. Issue 11 (8th August 2014) - Yahyaoui, N.; Sfina, N.; Lazzari, J.‐L.; Bournel, A.; Said, M.; Pizzini, Sergio; Kissinger, Gudrun
Abstract We report a theoretical investigation of strained Ge1−xSnx/Ge (001)‐oriented quantum wells as a bulding block in active region of infrared photodetector. The electronic band parameters, gaps, discontinuities and effective masses for heterointerfaces between compressively strained Ge1−xSnx and relaxed Ge have beencomputed at room temperature. From this preliminary and mendatory work, we conclude that pseudomorphic Ge1−xSnx alloys become direct band gap semiconductors at a Sn‐fraction of 15.3%, e.g. a lattice mismatch as high as 2.3%. Due to achievable critical layer thickness and mainly solid solubility limit, a type‐I compressively strained Ge/Ge0.92Sn0.08/Ge (double) quantum well is studied by solving Schrödinger equation without and applied bias voltage. A strong absorption coefficient (> 1×104 cm−1) and a Stark shift of the direct transition between 2.01 μm and 2.25 μm at large external fields (40kV/cm) are attractive characteristics for the design of infrared photodetectors (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)